2021
DOI: 10.3390/molecules26216640
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thiosemicarbazone Derivatives: In Vitro and In Silico Evaluation as Potential MAO-B Inhibitors

Abstract: MAO-B inhibitors are frequently used in the treatment of neurodegenerative diseases such as Parkinson’s and Alzheimer’s. Due to the limited number of compounds available in this field, there is a need to develop new compounds. In the recent works, it was shown that various thiosemicarbazone derivatives show hMAO inhibitory activity in the range of micromolar concentration. It is thought that benzofuran and benzothiophene structures may mimic structures such as indane and indanone, which are frequently found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Compounds containing N-heterocyclic skeletons are known to exhibit various biological and medicinal activities [30][31][32][33][34] . Among these compounds, pyrrole derivatives are generally shown to have several biological activities as antioxidant 35 , antifungal 36 , antituberculosis 37 , anti-inflammatory 38 , analgesic 39 , antidiabetic 40 and anticancer 41 agents. Some examples of pharmaceutical compounds with pyrrole ring skeletons are shown in Fig.…”
mentioning
confidence: 99%
“…Compounds containing N-heterocyclic skeletons are known to exhibit various biological and medicinal activities [30][31][32][33][34] . Among these compounds, pyrrole derivatives are generally shown to have several biological activities as antioxidant 35 , antifungal 36 , antituberculosis 37 , anti-inflammatory 38 , analgesic 39 , antidiabetic 40 and anticancer 41 agents. Some examples of pharmaceutical compounds with pyrrole ring skeletons are shown in Fig.…”
mentioning
confidence: 99%
“…The compound interaction hotspots, including the interactions of the polar thiocarbonyl moiety, resemble the modular composition of other previously described thiocarbazone lead compounds ( Osmaniye et al, 2021 ). While thiosemicarbazones currently attract significant interest as anticancer agents ( Baruffini et al, 2020 ), they also show antiviral activity against smallpox and other viruses ( Kune, 1964 ; Rogolino et al, 2015 ).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, it was observed that the compound containing benzofuran, one of the thiosemicarbazone derivatives synthesized by using benzofuran–benzothiophene rings, was more active. Therefore, in this study, new hybrid molecules were obtained by using benzofuran and thiazolylhydrazone pharmacophores. ,,, …”
Section: Introductionmentioning
confidence: 99%